Gender bias in customer perceptions: The case of agro-input dealers in Uganda - de, Anusha; Miehe, Caroline; Van Campenhout, Bjorn (Katholieke Universiteit Leuven, 2023)
Faced with incomplete and imperfect information, economic actors rely predominantly on perceptions and often base decisions on heuristics prone to bias. Gender bias in perceptions favoring men has been found in a wide variety of settings and may be an important reason why some sectors remain dominated by men, and gender gaps in terms of benefits persist. Using ratings of agro-input dealers provided by smallholder farmers in their vicinity, we test if farmers perceive male-managed agro-input shops differently than agro-input shops managed by women. After explicitly controlling for quality differences between male- and female-managed agroinput shops and including fixed effects to account for farmer-level heterogeneity, we find that farmers rate male-managed agro-input outlets higher on a range of attributes related to the dealership in general, as well as on the quality of inputs sold by the dealer. Our results show that gender bias in customer perceptions persists and continues to be a severe comparative disadvantage and an important entry barrier for female agro-input dealers. Policies and interventions designed to challenge gender norms and customs are needed to correct this bias.